Risk of death for young ex‐prisoners in the year following release from adult prison. (30th July 2013) - van Dooren, Kate; Kinner, Stuart A.; Forsyth, Simon
Abstract Background : In the community, all‐cause mortality rates among those younger than 25 years are considerably lower than those of older adults and are largely attributable to risk‐taking behaviours. However, given the unique health profiles of prisoners, this pattern may not be replicated among those leaving prison. We compared rates and patterns of mortality among young and older ex‐prisoners in Queensland, Australia. Methods : We linked the identities of 42, 015 persons (n=14, 920 aged <25 years) released from adult prisons in Queensland, Australia with the Australian National Death Index. Observations were censored at death or 365 days from release. We used Cox proportional hazards regression to explore associations between mortality and demographic and criminographic characteristics. We used indirect standardisation to compare rates of all‐cause mortality for both age groups with those for the general population. We calculated proportion of deaths across specific causes for each age group and relative risks for each cause for young versus older ex‐prisoners. Results : Being young was protective against death from all causes (AHR=0.7, 95% CI 0.5–0.8); however, the elevation in risk of all‐cause death relative to the general population was greater for those aged less than 25 years (SMR=6.5, 95% CI 5.3–8.1) than for older ex‐prisoners (SMR=4.0, 95% CI 3.5–4.5). Almost all deaths in young ex‐prisoners and the majority of those in older ex‐prisoners were caused by injury or poisoning. Conclusions : Young people are at markedly increased risk of death after release from prison and the majority of deaths are preventable.